A photosensitive surface capable of inducing electrophysiological changes in NG108-15 neurons. (15th January 2015) - Huang, Fei; Bladon, John; Lagoy, Ross C.; Shorrock, Peter N.; Hronik-Tupaj, Marie; Zoto, Christopher A.; Connors, Robert E.; Grant McGimpsey, W.; Molnar, Peter; Lambert, Stephen; Rittenhouse, Ann R.; Lambert, Christopher R.
Graphical abstract: Abstract: Retinal prostheses promise to be a viable therapy for many forms of blindness. Direct stimulation of neurons using an organic light-sensitive, self-assembled monolayer surface offers a simple alternative to conventional semiconductor technology. For this purpose we have derivatized an indium tin oxide (ITO) substrate with the photosensitive dye, NK5962, using 3-(aminopropyl)trimethoxysilane (APTMS) as cross-linker. The surface was characterized through contact angle goniometry, electrochemical impedance spectroscopy, grazing angle infrared and ultraviolet–visible spectrophotometry. NG108-15 neurons were grown on the ITO-APTMS-NK5962 surface and neural responses from electrical stimulation vs. photostimulation through the ITO-APTMS-NK5962 surface were measured using patch clamp electrophysiology. Under these conditions, photostimulation of depolarized cells caused an approximate 2-fold increase in voltage-gated sodium (Na + ) current amplitude at a membrane potential of −30 mV. Our results demonstrate the feasibility of stimulating neurons, grown on light-sensitive surfaces, with light impulses, which ultimately may facilitate the fabrication of a simple, passive retinal prosthetic.